2008
DOI: 10.1039/b802144a
|View full text |Cite
|
Sign up to set email alerts
|

Docking, synthesis, and NMR studies of mannosyl trisaccharide ligands for DC-SIGN lectin

Abstract: DC-SIGN, a lectin, which presents at the surface of immature dendritic cells, constitutes nowadays a promising target for the design of new antiviral drugs. This lectin recognizes highly glycosylated proteins present at the surface of several pathogens such as HIV, Ebola virus, Candida albicans, Mycobacterium tuberculosis, etc. Understanding the binding mode of this lectin is a topic of tremendous interest and will permit a rational design of new and more selective ligands. Here, we present computational and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…1). Previous studies have shown that DC-SIGN recognizes ␣(132)-linked dimannosyl and trimannosyl structures, with the affinity increasing with length (20,42,61). Furthermore, PIMs are present in the outermost layer of the mycobacterial cell envelope (54), where they function as adhesins for mycobacterial binding to both macrophages and nonphagocytic cells (36,47,71).…”
mentioning
confidence: 99%
“…1). Previous studies have shown that DC-SIGN recognizes ␣(132)-linked dimannosyl and trimannosyl structures, with the affinity increasing with length (20,42,61). Furthermore, PIMs are present in the outermost layer of the mycobacterial cell envelope (54), where they function as adhesins for mycobacterial binding to both macrophages and nonphagocytic cells (36,47,71).…”
mentioning
confidence: 99%
“…The NMR study was performed recording NOESY experiments in the absence and presence of DC-SIGN EDC (ensuring that DC-SIGN is a tetrameric aggregate), as well as STD NMR experiments for epitope mapping ( Fig. 1) [37].…”
Section: Std For Epitope Mappingmentioning
confidence: 99%
“…One of the major problems of docking algorithms in general is the identification of the correct conformation among the potential binding modes [100]. Therefore, computational docking approaches are frequently combined with wet-lab experiments, such as saturation transfer difference NMR (STD NMR) or transferred nuclear Overhauser effect (trNOE) spectroscopy [75,114116], to reliably assign the correct conformation of the ligand on the protein surface. Such combinations of experimental and theoretical approaches are also useful to determine the conformations of natural carbohydrates or their synthetic glycan mimetics [117119].…”
Section: Reviewmentioning
confidence: 99%